MSK Diagnostic Ultrasound for the Assessment of the Acromioclavicular Joint - Robert C Manske; Michael Voight; Phil Page; Chris Wolfe (International Journal of Sports Physical Therapy)
The acromioclavicular joint (ACJ), a key element in shoulder movement and stability, is prone to various injuries such as sprains, dislocations, and osteoarthritis, typically resulting from physical trauma or wear and tear. Accurate and timely diagnosis is paramount for effective treatment and rehabilitation. Musculoskeletal (MSK) ultrasound has emerged as a pivotal diagnostic tool due to its ability to visualize soft tissues and provide real-time imaging. This non-invasive tool is also invaluable for monitoring healing progress and the evolution of osteoarthritic changes. This article reviews the application of MSK ultrasound in the evaluation of ACJ injuries, highlighting its advantages, specific applications, and recent technological advancements that enhance its diagnostic capabilities.